On the Stability of Thin-Shell Wormholes in Noncommutative Geometry - Peter K. F. Kuhfittig (Advances in High Energy Physics)
This paper reexamines a special class of thin-shell wormholes that are unstable in general relativity in the framework of noncommutative geometry. It is shown that, as a consequence of the intrinsic uncertainty, these wormholes are stable to small linearized radial perturbations. Several different spacetimes are considered.